The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/0971-3026.116581
|View full text |Cite
|
Sign up to set email alerts
|

Acute Wallerian degeneration of middle cerebellar peduncles due to basilar artery thrombosis

Abstract: Wallerian degeneration (WD) is the process of demyelination and disintegration of the distal axonal segment following the interruption of the axonal integrity or damage to the neuron. We report a patient having WD of middle cerebellar peduncles due to pontine infarction caused by basilar artery thrombosis. We review the anatomy and discuss the pathogenesis of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…[ 10 ] In this study, bilateral MCPs lesions appeared after the unilateral and isolated infarction involving the ventral pons without additional abnormalities, which is consistent with the diagnosis of WD of MCPs, owing to damage of the above-mentioned anatomical structures. In addition, it has been reported that the primary infarction often involves the basis pontis, and that paramedian pontine infarction is the most common location,[ 3 7 11 12 13 14 ] which is consistent with observations in this study. Moreover, the BA in previously reported cases was normal,[ 11 ] or exhibited atherosclerosis plaque formation,[ 12 ] severe stenosis, or occlusion.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…[ 10 ] In this study, bilateral MCPs lesions appeared after the unilateral and isolated infarction involving the ventral pons without additional abnormalities, which is consistent with the diagnosis of WD of MCPs, owing to damage of the above-mentioned anatomical structures. In addition, it has been reported that the primary infarction often involves the basis pontis, and that paramedian pontine infarction is the most common location,[ 3 7 11 12 13 14 ] which is consistent with observations in this study. Moreover, the BA in previously reported cases was normal,[ 11 ] or exhibited atherosclerosis plaque formation,[ 12 ] severe stenosis, or occlusion.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the BA in previously reported cases was normal,[ 11 ] or exhibited atherosclerosis plaque formation,[ 12 ] severe stenosis, or occlusion. [ 13 ] In this study, BA lesions were also nonspecific; thus, we suspect that the etiology of pons infarction might have been small vascular disease, atherosclerotic stenotic disease of the BA, or branch artery disease.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations